THE SEARCH WARRANT PROVISIONS OF THE CYBERCRIMES ACT AND THEIR RELATIONSHIP WITH THE CRIMINAL PROCEDURE ACT - Du Toit, Pieter Gerhardus (Obiter, 2023)
The recently enacted Cybercrimes Act 19 of 2020 regulates the powers of the police and investigators to investigate cybercrimes. Chapter 4 of the Act provides for the powers of the police and others in respect of search, access or seizure in the investigation of cybercrimes and other offences committed by means of cybertechnology. The provisions of the Criminal Procedure Act 51 of 1977 will continue to operate in addition to the provisions of the Cybercrimes Act, to the extent that the Criminal Procedure Act is not inconsistent with the Cybercrimes Act. The search and seizure provisions of the Criminal Procedure Act are object-based, as they do not deal explicitly with the specialised procedures that are required to investigate cybercrimes or other offences that involve the use of digital devices. The Cybercrimes Act attempts to address this shortcoming. The coexistence of the search and seizure provisions in these two Acts may cause difficulties in the fight against crime. In addition to the validity requirements of search warrants, as set out in the Acts, additional intelligibility requirements for the validity of search warrants have been developed by the courts.